Extracellular Vesicles as Biomarkers in Infectious Diseases - Cinthia Gonzalez Cruz; Husain M. Sodawalla; Thalachallour Mohanakumar; Sandhya Bansal (Biology)
Extracellular vesicles (EVs) are nanosized vesicles that are secreted by all cells into the extracellular space. EVs are involved in cell-to-cell communication and can be found in different bodily fluids (bronchoalveolar lavage fluid, sputum, and urine), tissues, and in circulation; the composition of EVs reflects the physiological condition of the releasing cell. The ability to use EVs from bodily fluids for minimally invasive detection to monitor diseases makes them an attractive target. EVs carry a snapshot of the releasing cell’s internal state, and they can serve as powerful biomarkers for diagnosing diseases. EVs also play a role in the body’s immune and pathogen detection responses. Pathogens, such as bacteria and viruses, can exploit EVs to enhance their survival and spread and to evade detection by the immune system. Changes in the number or contents of EVs can signal the presence of an infection, offering a potential avenue for developing new diagnostic methods for infectious diseases. Ongoing research in this area aims to address current challenges and the potential of EVs as biomarkers in diagnosing a range of diseases, including infections and infectious diseases. There is limited literature on the development of EVs as diagnostic biomarkers for infectious diseases using existing molecular biology approaches. We aim to address this gap by reviewing recent EV-related investigations in infectious disease studies.